2022
DOI: 10.7731/kifse.4e23ccc1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics of Scattering Ratio Based on Three Optical Wavelengths for Smoke Particles

Abstract: Photoelectric smoke detectors, which operate by reacting to the scattering of light caused by particles entering the light path, are widely used and extremely sensitive. Owing to higher standards imposed by Underwriters Laboratories, researchers have begun analyzing the properties of smoke particles. In particular, several wavelengths are used to classify particles by their scattering reactivity. The performances of actual smoke detectors are limited by their hardware and price. Therefore, properties that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Subsequently, it can be observed that they reach a saturation point at a constant level and exhibit fluctuations. Note that this pattern is not limited to the experiments conducted in this paper but is observed in studies involving scattering signal collection through optical detectors, including similar fire tests [12,17]. Based on these shapes of signals, we extract data using three methods.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Subsequently, it can be observed that they reach a saturation point at a constant level and exhibit fluctuations. Note that this pattern is not limited to the experiments conducted in this paper but is observed in studies involving scattering signal collection through optical detectors, including similar fire tests [12,17]. Based on these shapes of signals, we extract data using three methods.…”
Section: Methodsmentioning
confidence: 90%
“…Focusing on the correlation between different wavelengths, it is possible to develop technologies for detecting non-fire sources or distinguishing smoke particles using light sources at various wavelengths. In [12], research focused on extracting characteristic values through the statistical analysis of correlations among multiple wavelengths, while [13] explored the discrimination of smoke particles using signals from multiple wavelengths. In the realm of products, both TI's TPS8802 [14] and Analog Devices' ADPD188BI [15] introduce modules that are based on the scattering efficiency between dual wavelengths, aiming not only for fire detection but also for distinguishing non-fire sources.…”
Section: Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, a smoke detector capable of detecting the scattering intensity of smoke particles was utilized [14,15]. In a previous experiment, a smoke detector was adopted to repeatedly measure the scattering intensity of light with multiple optical wavelengths [16]. The scattering intensity of smoke particles derived from each source indicates the unique characteristics of the sources.…”
Section: Multiple Optical Wavelengths-based Smoke Detectormentioning
confidence: 99%
“…In this study, a previous fire experimental dataset was collected. The fire experiment was conducted in the same manner as that in the experiment conducted by Han et al [16] in the same experiment chamber. The chamber is a carbon-steel square duct with dimensions of   ×      .…”
Section: Previous Experiments Dataset For Data Collectionmentioning
confidence: 99%